Assay of Some Antimalarial Drugs in Pure Form and in Their Pharmaceutical Preparations with Pyridinium Fluorochromate Reagent - K. Singh, Brijesh; Kumar, Vinod; Shukla, I.C. (Asian Journal of Chemistry, 2013)
In the present paper, we have reported a simple and convenient titrimetric method for determination of antimalarial drugs e.g., chloroquine phosphate, amodiaquine hydrochloride, mefloquine hydrochloride, primaquine phosphate and quinine sulphate in pure form and in their pharmaceutical preparations such as lariago, resochin, camoquin, flavoquine, mefloquin, meflotas, maliride, malquine, quinersol and rezquine tablets with pyridinium fluorochromate reagent. It is a versatile oxidizing agent of chromium(VI) and is being widely used as an oxidant for several classes of organic compounds. During estimation it was noted that the excipients present in pharmaceutical preparations do not interfere. The value of percentage error, coefficient of variation and standard deviation prove the method to be precise and reproducible. To establish authenticity of the method, recovery experiments were also carried out by standard drug addition method.